PENANAMAN KARAKTER RELIGIUS ANAK MELALUI PENGAJIAN KITAB AKHLAK LIL BANIN DI PONDOK PESANTREN DARUL INABAH - Indra Permana; Ema Aprianti; Novi Widiastuti; Prita Kartika (Comm-Edu (Community Education Journal), 2026)
This study aims to explore how the religious character of children is cultivated through the study of the Akhlak Lil Banin book at Pondok Pesantren Darul Inabah, located in Sukasari Village, Gununghalu District, West Bandung Regency. The background of this research is rooted in the urgent need for religious character education as a fundamental aspect in shaping children's personalities amidst the challenges of globalization and technological advancement, which often negatively affect moral values among the younger generation. The research adopts a mix methods approach with a convergent design, combining both qualitative and quantitative data collection. Data were gathered through direct observation of the religious study sessions and in-depth interviews with five key informants: a student, a teacher, a boarding school supervisor, a parent, and the head of the pesantren. Qualitative data were analyzed using the Miles & Huberman interactive model, while quantitative data were analyzed descriptively. The findings reveal that the study of Akhlak Lil Banin is conducted regularly and systematically,  using communicative  and  contextual  teaching  methods.  Religious  values  such  as honesty, politeness, responsibility, and discipline are instilled through habituation and role modeling. Students showed positive changes in behavior and increased religious awareness. The conducive pesantren environment also played a significant role in reinforcing these values in their daily lives. The study concludes that the Akhlak Lil Banin study program serves as an effective medium for instilling religious character in children and can be used as a model for character education in other Islamic educational institutions.